2015
DOI: 10.1039/c5ra15348d
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube-based QuEChERS extraction and enhanced product ion scan-assisted confirmation of multi-pesticide residue in dried tangerine peel

Abstract: A sorbent package consisting of a combination of multiwalled carbon nanotubes (MWNTs) and a primary secondary amine (PSA) has been used for a modified quick, easy, effective, rugged, and safe (QuEChERS) extraction of 104 pesticides from dried tangerine peel samples. MWNTs and graphitized carbon black (GCB) have been compared in terms of purification efficiency and recovery; the best results were achieved with MWNTs. The pesticides were quantified on a liquid chromatography tandem mass spectrometry (LC-MS/MS) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 37 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…5 Our previous study also showed the tangerine peels were contaminated with multiresidues. 6 The citrus plant and fruit are prone to pest infection such as pathogens, mites and aphids, insecticides are heavily used for field, plant and post-harvest protection, especially in the upcoming harvest time. Awareness about the frequent residues and potential health hazards has promoted the demand for persistent and highly poisonous organic pesticides detection, 7 particularly organochlorines (OCPs), organophosphates (OPPs) and pyrethroids (PYHs) in the plant-originated product.…”
Section: Introductionmentioning
confidence: 99%
“…5 Our previous study also showed the tangerine peels were contaminated with multiresidues. 6 The citrus plant and fruit are prone to pest infection such as pathogens, mites and aphids, insecticides are heavily used for field, plant and post-harvest protection, especially in the upcoming harvest time. Awareness about the frequent residues and potential health hazards has promoted the demand for persistent and highly poisonous organic pesticides detection, 7 particularly organochlorines (OCPs), organophosphates (OPPs) and pyrethroids (PYHs) in the plant-originated product.…”
Section: Introductionmentioning
confidence: 99%